2019
DOI: 10.3390/ijms21010126
|View full text |Cite
|
Sign up to set email alerts
|

Promising New Inhibitors of Tyrosyl-DNA Phosphodiesterase I (Tdp 1) Combining 4-Arylcoumarin and Monoterpenoid Moieties as Components of Complex Antitumor Therapy

Abstract: Tyrosyl-DNA phosphodiesterase 1 (Tdp1) is an important DNA repair enzyme in humans, and a current and promising inhibition target for the development of new chemosensitizing agents due to its ability to remove DNA damage caused by topoisomerase 1 (Top1) poisons such as topotecan and irinotecan. Herein, we report our work on the synthesis and characterization of new Tdp1 inhibitors that combine the arylcoumarin (neoflavonoid) and monoterpenoid moieties. Our results showed that they are potent Tdp1 inhibitors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 79 publications
1
43
0
Order By: Relevance
“…Some of these derivatives exhibit analgesic, antiviral, neuroprotective, and antitumor properties [ 14 ]. Moreover, new classes of TDP1 inhibitors with submicromolar half maximal inhibitory concentration (IC 50 ) values have been developed that contain monoterpene moieties; for example, coumarin [ 16 ], 4-arylcoumarin [ 17 ], and adamantane [ 18 , 19 , 20 , 21 ] derivatives as well as octahydro-2 H -chromenes 3 (see Figure 1 ) synthesized from p -menthane monoterpenoid (-)-isopulegol [ 22 ]. Their ability to enhance the Tpc cytotoxic potential was demonstrated for several of these derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these derivatives exhibit analgesic, antiviral, neuroprotective, and antitumor properties [ 14 ]. Moreover, new classes of TDP1 inhibitors with submicromolar half maximal inhibitory concentration (IC 50 ) values have been developed that contain monoterpene moieties; for example, coumarin [ 16 ], 4-arylcoumarin [ 17 ], and adamantane [ 18 , 19 , 20 , 21 ] derivatives as well as octahydro-2 H -chromenes 3 (see Figure 1 ) synthesized from p -menthane monoterpenoid (-)-isopulegol [ 22 ]. Their ability to enhance the Tpc cytotoxic potential was demonstrated for several of these derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to enhance the Tpc cytotoxic potential was demonstrated for several of these derivatives. For example, 7-hydroxycoumarin derivative 4 ( Figure 1 ) with a pinene-type fragment reduced the CC 50 (median cytotoxic concentration causing 50% cell death) of camptothecin eight-fold for the human breast adenocarcinoma cell line MCF-7 [ 16 ] while the hybrid molecule 5 , comprising of (4-fluorophenyl)-coumarin and geraniol moieties, showed a significant increase in the antitumor effect of Tpc on Krebs-2 ascites in an in vivo tumor model [ 17 ]. Among the adamantane derivatives, strong synergism was found for 6 and 7 ( Figure 1 ), both containing the acyclic monoterpene substituents, when lung adenocarcinoma cells A549 were treated in combination with Tpc [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, natural products of various types have been found to inhibit Tdp1, including derivatives of bile acids 4 [ 10 , 11 ], of lichen metabolite usnic acid 5a , b [ 12 , 13 ] and 6 [ 14 ], monoterpenoid derivatives 7 [ 15 , 16 , 17 , 18 ] and oxinitidine 8 [ 19 ] with inhibitory activity in the micro- or submicromolar range. Importantly, the hydrazinothiazole derivative of usnic acid 5a [ 13 , 20 ] and monoterpene-substituted 4-arylcoumarin 7a [ 21 ] significantly increased topotecan efficacy in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, we have previously shown that various Tdp1 inhibitors enhanced the cytotoxic and antitumor effects of topotecan [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In this work, we also tested the ability of the berberrubine sultones to sensitize cells to the action of topotecan.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Tdp1 is a promising therapeutic target, and its inhibitors are expected to significantly synergize the effects of current anti-tumor therapies, including topoisomerase poisons and other DNA damaging agents. Indeed, it was found that combined treatment of tumor cells with Tdp1 inhibitors and anticancer drugs camptothecin or topotecan greatly increased the activity of these pharmaceuticals in in vitro [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and in vivo [ 29 , 30 ] experiments. Nevertheless, to the best of our knowledge, no Tdp1 inhibitors have reached human clinical trials.…”
Section: Introductionmentioning
confidence: 99%